An Ambitious Failure: Conceptualising the EU Approach to Rule of Law Promotion (in Ukraine). (January 2014) - Burlyuk, Olga
Abstract : This article conceptualises the EU approach to rule of law promotion outside of accession, taking Ukraine as a case study. Empirical evidence, collected through document analysis, expert interviews and participant observation, reveals that the rule of law as a legal and political category in EU external relations has little to do with the essentialist scholarly definitions of the concept. Instead, it constitutes an abstract ideal which frames bilateral cooperation at the political level and a banner under which the parties realise a variety of activities at the practical level. This EU approach is deliberate and meant to allow for defining the rule of law in harmony with the parties' integration ambitions, priorities and domestic institutional contexts. The article concludes with a discussion of the findings' implications for future policy and research.